Comment on "An asymptotic analysis of composite beams with kinematically corrected end effects" by Jun-Sik Kim, Maenghyo Cho and Edward C. Smith [Int. J. Solids Struct. 45 (2008) 1954–1977]. (1st June 2015) - Kovvali, Ravi Kumar; Hodges, Dewey H.; Yu, Wenbin
Abstract: In their paper Kim et al. (2008), Kim, Cho and Smith presented predictions that exhibited significant differences in bending-shear coupling for the CUS box beam from their own analysis (FAMBA) vis-à-vis from VABS (Yu et al., 2002, 2012). The actual differences between results obtained from VABS (Yu et al., 2002, 2012) and FAMBA, when executed properly, are shown herein to be very minor. Indeed, both stiffness models yield very acceptable results for a static analysis. Specifically, VABS does not significantly deviate, qualitatively or quantitatively, from 3D FEM predictions, in contrast to results presented in Kim et al. (2008).